Large Platelet and Endothelial Extracellular Vesicles in Cord Blood of Preterm Newborns: Correlation with the Presence of Hemolysis - Andrea Hujacova; Jan Sirc; Kristyna Pekarkova; Tereza Brozova; Marie Kostelanska; Jakub Soukup; Tibor Mosko; Karel Holada; Zbynek Stranak (Diagnostics, 2021)
Different biomarkers are investigated to detect the causes of severe complications in preterm infants. Extracellular vesicles (EVs) are recognized as an important part of cell-to-cell communication, and their increased levels were reported in numerous pathological states. We aimed to increase our knowledge about the incidence of platelet and endothelial EVs in cord blood of preterm newborns using conventional flow cytometry. The presence of platelet (CD36+CD41+), activated platelet (CD41+CD62+), and endothelial (CD31+CD105+) EVs was analyzed. Immune electron microscopy was used to confirm the presence of EVs and the specificity of their labeling. The size of detected extracellular vesicles was in the range 400–2000 nm. The differences in the counts of EVs between the preterm and control group were not significant and no correlation of EVs count with gestation age was recorded. Cord blood plasma samples with free hemoglobin level > 1 mg/mL had more than threefold higher counts of CD36+CD41+ and CD41+CD62+ EVs (p < 0.001), while the count of CD31+CD105+ EVs was only moderately increased (p < 0.05). Further studies utilizing cytometers with improved sensitivity are needed to confirm that the analysis of large platelet and endothelial EVs mirrors the quantitative situation of their whole plasma assemblage.